ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - restian septiana; Yusti Sylivia Febriarini; Luvy Sylviana Zanthy (IKIP Siliwangi, 2019)
This study aims to determine the mathematical critical thinking ability of junior high school students in Rancabali District with indicators of the mathematical critical thinking ability of students used to understand the problem, provide arguments, induce and the ability to make decisions or actions. The ability of mathematical critical thinking is the ability to think that aims to make decisions or actions that make sense through what is believed to be truth and can be done correctly. This research was conducted on 10 students in one junior high school in Rancabali District by using a qualitative descriptive method. The instrument used in the form of 4 items about students' mathematical critical thinking skills on the material to build flat side spaces accompanied by interviews with students. The conclusion of this study is the mathematical critical thinking ability of junior high school students in Rancabali District is still very low.